Distancing the Dead Late Chalcolithic Burials in Large Maze Caves in the Negev Desert, Israel - Davidovich, Uri; Marom, Nimrod; Abramov, Julia; Frumkin, Amos 1953-; Langford, Boaz; Langgut, Dafna; Ullman, Micka; Yahalom-Mack, Naama (2018)
The Late Chalcolithic of the southern Levant (ca. 4500-3800 B.C.E.) is known for its extensive use of the subterranean sphere for mortuary practices. Numerous natural and hewn caves, constituting formal extramural cemeteries, were used as secondary burial localities for multiple individuals, reflecting and reaffirming social order and/or communal identity and ideology. Recently, two large complex caves located in the northern Negev Highlands, south of the densely settled Late Chalcolithic province of the Beersheba Valley, yielded skeletal evidence for secondary interment of select individuals accompanied by sets of material culture that share distinct similarities. The observed patterns suggest that the interred individuals belonged to sedentary communities engaging in animal husbandry, and they were deliberately distanced after their death, both above-ground (into the desert) and underground (deep inside subterranean mazes), deviating from common cultural practices.
Keywords: Ashalim Cave; Chalcolithic; Levant; Qina Cave; animal husbandry; cave burials; mortuary practices; social deviancy